FRI0145 The effect of adalimumab on risk of major adverse cardiovascular events in rheumatoid arthritis: A meta-analysis of randomized trials. (23rd January 2014) - Burmester, G.; Emery, P.; Signorovitch, J.; Williams, D.; Valdes, J.; Bao, Y.; Mulani, P.M.
Abstract : Background: Patients with rheumatoid arthritis (RA) have greater cardiovascular (CV) morbidity compared with the general population. Blockade of the pro-inflammatory cytokine tumor necrosis factor-α (TNF) by anti-TNF therapies has been hypothesized to reduce CV risk, and use of these agents has been associated with reduced risk of CV events in some observational studies. Objectives: To assess the effect of adalimumab (ADA), a TNF inhibitor, in combination with methotrexate (MTX) vs. MTX alone on risk of major adverse CV events (MACEs) in patients with RA. Methods: This meta-analysis included data from individual patients with RA randomized to double-blind treatment with combination therapy of ADA+MTX vs. MTX monotherapy in Phase II/III clinical trials (ARMADA, DE019, PREMIER, and OPTIMA [first double-blind period]); the maximum double-blind trial duration was 2 years. All patients who received at least one dose of study drugs were included. The primary outcome was the time from baseline to a MACE, a composite of nonfatal myocardial infarction (MI), nonfatal stroke, and CV death. These component events were also studied separately. Events were adjudicated by a blinded external panel of 2 cardiologists and 1 neurologist. Times to events were compared between the ADA+MTX and MTX arms using Kaplan-Meier estimates of the cumulative risk and Cox proportional-hazards models stratified by trial. The sequential Holm procedure was used to account for testing of each MACE component. Multivariable Cox models were also applied, with stratification by trial and adjustment for baseline age, sex, body mass index, blood pressure, total cholesterol, history of diabetes, history of MI or stroke, and prior use of statins or antihypertensive drugs. Results: A total of 1411 patients on ADA+MTX combination therapy and 1036 on MTX monotherapy were included in the study. Sixty-four percent of these patients (n=1557) were MTX naïve. Mean age was 53 years; 74% of patients were female. A total of 15 MACEs occurred: 5 in the ADA+MTX arm (2 nonfatal MIs, 2 nonfatal strokes, and 1 CV death) and 10 in the MTX monotherapy arm (7 nonfatal MIs, 2 nonfatal strokes, and 1 CV death). Compared with MTX monotherapy, ADA+MTX combination therapy was associated with a significant 66% reduction in the hazard of MACE (hazard ratio [HR]=0.33, 95% confidence interval [CI]=0.12–0.95, P =.04 [table ]) and a significant 84% reduction in the hazard of nonfatal MI (HR=0.16, 95% CI=0.04–0.63, P =.008). Hazards of stroke and death did not differ significantly between the treatment arms, nor did the overall rates of serious adverse events. Findings were robust to adjustment for baseline characteristics. Conclusions: Compared with MTX monotherapy, ADA+MTX combination therapy showed a statistically significant lower occurrence of MACE, a composite of nonfatal MI, nonfatal stroke, and CV death, during up to 2 years of treatment, with the difference mainly driven by a statistically significant lower hazard ratio for nonfatal MI. Disclosure of Interest: G. Burmester Grant/Research support from: Abbott, Consultant for: Abbott, Speakers Bureau: Abbott, P. Emery Consultant for: Abbott, J. Signorovitch Consultant for: Abbott (Analysis Group is under contract), Employee of: Abbott, D. Williams Shareholder of: Abbott, Employee of: Abbott, J. Valdes Shareholder of: Abbott, Employee of: Abbott, Y. Bao Shareholder of: Abbott, Employee of: Abbott, P. Mulani Shareholder of: Abbott, Employee of: Abbott